Implementasi Metode Pembelajaran Future Planning (Pengembangan Konseling Yang Berorientasi Pada Perencanaan Masa Depan) Untuk Meningkatkan Prestasi Belajar Siswa di SMA Negeri 1 Sooko, Kabupaten Ponorogo - Mukh. Aslam Ashuri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
The purpose of this research is the researcher wants to know whether the learning method of Future Planning (The improvement of counseling which oriented at Future Planning) constantly able to increase students achievement at students’ basic competence which have knowledge about their psychology condition. Based on the result of classroom action research (CAR) generally doing the learning method of Future Planning (The improvement of counseling which oriented at Future Planning) the students able to have knowledge about their psychology condition. The researcher have done at students in class X-Natural Science-1 odd semester at Senior High School state 1 Sooko, Ponorogo regency in academic year 2018/2019. Based on the classroom action research each cycles, start from 1st cycle, 2nd cycle, until 3rd cycle always increase that the students have knowledge about psychology condition. This is can be identified from the result of average value which have gotten from students, grouping or individually. The students have knowledge of psychology condition is a adroitness, so in many trying frequently surely it will increase the result students achievement in doing the learning method of Future Planning (The improvement of counseling which oriented at Future Planning). This is can be identified at 1st cycle, 2nd, and 3rd sequence, it can be concluded that the students which have active activity in average is 26.48 (26%) 1st cycle, 41.18 (41%) 2nd cycle, 81.41 (82%) 3rd cycle and the students which did not active showed 83.52 (84%) 1st cycle, 58.82 (59%) 2nd cycle, 20.58 (21%) 3rd cycle, and the students which done the learning method of Future Planning (The improvement of counseling which oriented at Future Planning) which have good character is 11.86 (12%) 1st cycle, 38,23 (38%) 2nd cycle, 10.18 (10%) 3rd cycle and in less character showed 88.23 (88%) 1st cycle, 61.86 (62%) 2nd cycle, 8.82 (9%) 3rd cycle and the result of students achievement have average value is 62.32 (62%) 1st cycle, 64.02 (64%) 2nd cycle, 85.220 (85 %) 3rd cycle. Because of it is still up of students passing grade (SPG) 80 (80 %) which have decision, so this research activity did not need to do the researcher at next cycles. So that in this researcher declared Finish or Success.